Effect of Smoking and Grilling on Polycyclic Aromatic Hydrocarbons in Ghanaian Tilapia - Bismark Dwumfour-Asare; Emmanuel Dartey; Nomolox Solomon Kofi Adherr; Kofi Sarpong; Emmanuel Agyapong Asare (SAGE Publishing, 2023)
The study assessed 18 Polycyclic Aromatic Hydrocarbons (PAHs) in O. niloticus (Nile tilapia) sampled from an aquaculture cage (farm) and a wild catch. The PAHs in fish samples were analysed using Gas Chromatography-Mass Spectrometry. Four PAHs (in order of levels: Indeno [1,2,3-cd] pyrene > Anthracene > Perylene > Pyrene; 100-0.8 µg/kg) and only one PAH (Pyrene: 4 µg/kg) were detected in raw samples from the cage and wild catch respectively. Chargrilling significantly increased Pyrene levels after cooking (wild: 4-11 µg/kg; cage: 5-23 µg/kg, p  < .05), and likewise Anthracene levels in cage samples (13-153 µg/kg) but decreased Indeno [1,2,3-cd] pyrene levels from 100 ± 20 to 1.2 ± 0.2 µg/kg in cage samples. Smoking significantly increased 13 to 15 PAH congeners' levels (from < 1.0 up to 340 µg/kg) and total PAHs (wild: 4 to 840 µg/kg; cage: 110 to 560 µg/kg), and decreased Indeno [1,2,3-cd] pyrene (100 to 1.3 µg/kg) in cage samples but showed no effect on Benzo [g, h, i] perylene and Dibenzo [a, h] anthracene levels in all samples. For smoked samples, Benzo [a] pyrene and PAH4 (Benzo [a] anthracene, Chrysene, Benzo [b] fluoranthene, and Benzo [a] pyrene) exceeded the respective maximum permissible limits of 2 µg/kg and 12 µg/kg, and significantly influenced the levels of carcinogenic PAHs (CPAH, 135-170 µg/kg). Nevertheless, the Excess Cancer Risk (ECR) estimates, from a conservative approach, were far below the threshold (10 −4 ), implying that consuming smoked or grilled tilapia from the study site is safe.